Mangrove Ecosystem Degradation Level in Kaledupa Island, Wakatobi National Park TINGKAT DEGRADASI EKOSISTEM MANGROVE DI PULAU KALEDUPA, TAMAN NASIONAL WAKATOBI - Agusrinal .; Nyoto Santoso; Lilik Budi Prasetyo (Jurnal Silvikultur Tropika, 2015)
The study was aimed to analyze mangrove deforestation and degradation level and to analyze mangrove species composition and diversity in Kaledupa Island Wakatobi National Park. Some analysis done in this study were: GIS analysis with ERDAS and ArcMap software, vegetation analysis by line transect and plot methods. The results showed that mangrove deforestation is happened since 1996 untill 2014 as wide as 214.04 hectares. Mangrove ecosystem at Kaledupa Island was damaged. Vegetation analysis results showed that there found eight species of mangroves, i.e. six species are in the Tanomeha Village, five species found at Horuo-Tampara Village and seven species found respectively at Balasuna and Lewuto Villages. Rhizophora apiculata Bl., Rhizophora mucronata Lamk. Ceriops tagal (Perr.) C. B. Rob. and Sonneratia alba Smith. were dominant tree species at Tanomeha, Balasuna, Lewuto and Horuo-Tampara Villages, respectively. Causative factors of mangrove degradation were economic factors, low education and skills, and lack of control of the authorities.Key words: deforestation, degradation, mangrove ecosystem.